Fintech as a catalyst for economic growth and sdg attainment: the role of fdi across income level economies - Ng, Loo Hui (2025)
Although FDI and FinTech are increasingly acknowledged as important development drivers, their effects are complicated, and empirical results are frequently contradictory and inconsistent among nations with different income levels. Despite extensive research, existing research often analyzes FinTech and FDI in isolation, overlooking their combined effects and the mediating role of FDI in translating financial innovation into broader development outcomes. Additionally, many studies use limited indicators for FinTech and focus on individual SDGs rather than their aggregate impact, creating a gap in holistic understanding. Consequently, this research aims to compare FinTech development across income levels and to examine both the direct and indirect impacts of FinTech and FDI on macroeconomic performance and SDG attainment. Specifically, this research utilizes a balanced panel dataset for 54 countries, categorized into four income groups, covering the period from 2017 to 2023. Specifically, this research will employ descriptive statistics, the Kruskal-Wallis Test, and panel regression models to test the hypotheses. Overall, the study finds that FinTech development remains in its infant stage, particularly in lower-income economies. Consequently, the relationship between FinTech and FDI is insignificant, and the effect of FDI on economic performance and SDG achievement is limited, with significance observed only for HFCE and GFCF. However, the most significant finding of this research is the strong and positive effect of FinTech on SDG achievement. Therefore, this study provides a comprehensive understanding of how financial innovation can be leveraged to promote sustainable development and offers evidence-based insights for government policymakers and financial firms to design more effective, context specific strategies.